A prospective observational study on recurrent pregnancy loss and its causes - Patel, Himani R.; Myangar, Mansi M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Our objective was to study and evaluate the causes of recurrent pregnancy loss. Methods: A prospective observational study was done over a period of 6 months from July-December 2022 at the department of obstetrics and gynecology at BJ Medical College. It was observed that out of 3124 total deliveries, 40 patients had the history of recurrent pregnancy loss (1.2%). Results: Out of total 3125 deliveries, 40 patients were identified with the above mentioned criteria, and the incidence level of recurrent pregnancy loss was calculated to be 1.2%. The results obtained were compiled and tabulated to observe that the maximum number of cases fell in the age group of 26-30 years and 70% of them belonged to the urban areas. 65% cases had primary pregnancy loss and 35% had secondary pregnancy loss. Second trimester losses were seen in 57.5% cases. The causes of the recurrent pregnancy loss were identified and categorised, where it was identified that uterine anomaly contributed to a large number of cases (30%). Conclusions: Detailed work up to identify the cause like blood investigations for analysing endocrine causes, USG/ MRI to identify uterine structural anomalies, genetic analysis and karyotyping of the fetus and both the parents to identify the genetic causes were carried out. Apart from treating the underlying causes, psychological counselling of the couple also becomes necessary. Lifestyle modification should always be advised to couples with such history.